Aplikasi Digital Risalah Ilmu Tajwid dalam Meningkatkan Kemampuan Baca Alquran - Khairul, Khairul; Haramain, Muhammad (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2018)
This article discusses the using of risalah of tajwid digital apps in increasing the students of SMA Negeri 4 Pinrang abilities in reading al-Qur’an. The using of risalah of tajwid digital apps was by optimazing the technology of computer that running by risalah of tajwid digital apps, that able to create the learning environment to prepare the options that can stimulated the students to use the potential cognitive. The objectives of this research was to get the empirical data about the students’ ability in reading Alquran before and after taught by using risalah digital of tajwid science and to get the empirical data about students’ ability in reading Alquran before and after using text book as well as to get the information about the difference in students’ level of ability in reading Alquran at the experiment class and the control class. The research design is used nonequivalent control group design, it means that in this design the experiment class nor the control class was not selected randomly.The research results are: (1) The level of students’ ability in reading Alquran in the experiment class before the treatment was classified in poor category, however, after given the treatment it was in good category. (2) The level of students’ ability in reading Alquran in the control class before the treatment was in poor category, however, after given the treatment it was in good category. (3) There are difference of students’ level ability in reading Alquran in the experiment class and the control class.